Problems in Writing Spoof Texts - Nurma Dhona Handayani; Khairul Harha (Universitas Syiah Kuala, 2016)
A spoof tells a story with a humorous twist or an unpredictable and usually funny ending. It is usually a story that could have happened in the past which has a social function to entertain and give a moral message to the readers/listeners. This research used a mix method to find out students’ problems in writing spoofs, especially problems with text organization and language features. The results are expected to be useful for other teachers and for students faced with writing a spoof. The population for this study was the third year students at a high school in Padang and the sample two classes were selected by using a stratified cluster random sample technique. The researcher used a writing task as the research instrument to obtain the data. Based on the data, it was found that more than 50% of the students in the sample had problems in writing a spoof. It can be suggested that writing comprehension and characteristic of texts should be taught in various techniques and strategies so that the students are able to understand and apply them in a good writing.